Women making modernism - Delsandro, Erica Gene (University Press of Florida, 2020)
Challenging the tendency of scholars to view women writers of the modernist era as isolated artists who competed with one another for critical and cultural acceptance, Women Making Modernism reveals the robust networks women created and maintained that served as platforms and support for women's literary careers. The essays in this volume highlight both familiar and lesser-known writers including Virginia Woolf, Mina Loy, Dorothy Richardson, Emma Goldman, May Sinclair, and Mary Hutchinson. Their examples show how women's writing communities interconnected to generate a current of energy, innovation, and ambition that was central to the modernist movement. Amplifying the reality of women's contributions to modernism, this volume advocates for an "orientation of openness" in reading and teaching literature from the period, helping to ease the tensions between feminist and modernist studies.